Does impaired socioemotional functioning account for behavioral dysexecutive disorders? Evidence from a transnosological study. Issue 1 (2nd January 2017) - Narme, Pauline; Roussel, Martine; Mouras, Harold; Krystkowiak, Pierre; Godefroy, Olivier
ABSTRACT: Behavioral dysexecutive disorders are highly prevalent in patients with neurological diseases but cannot be explained by cognitive dysexecutive impairments. In fact, the underlying mechanisms are poorly understood. Given that socioemotional functioning underlies appropriate behavior, socioemotional impairments may contribute to the appearance of behavioral disorders. To investigate this issue, we performed a transnosological study. Seventy-five patients suffering from various neurological diseases (Alzheimer's disease (AD), Parkinson's disease (PD), frontotemporal lobar degeneration, and stroke) were included in the study. The patients were comprehensively assessed in terms of cognitive and behavioral dysexecutive disorders and socioemotional processes (facial emotion recognition and theory of mind). As was seen for cognitive and behavioral dysexecutive impairments, the prevalence of socioemotional impairments varied according to the diagnosis. Stepwise logistic regressions showed that (i) only cognitive executive indices predicted hypoactivity with apathy/abulia, (ii) theory of mind impairments predicted hyperactivity–distractibility–impulsivity and stereotyped/perseverative behaviors, and (iii) impaired facial emotion recognition predicted social behavior disorders. Several dysexecutive behavioral disorders are associated with an underlying impairment in socioemotional processes but not with cognitive indices of executive functioning (except for apathy). These results strongly suggest that some dysexecutive behavioral disorders are the outward signs of an underlying impairment in socioemotional processes.